Multipath routing and brokering in inter-domain or inter-as with SDN: A model - Abe, John Olorunfemi; Mantar, Hac Ali (IEEE, 2017)
The problems associated with multipath routing in Border Gateway Protocol (BGP) for Autonomous Systems (ASes) can be solved with some model or control systems from the Software Defined Networking (SDN). The SdN controller could be used to solve the inconsistencies in the scalability and latency of the Routing Information Base (RIB) of ASes. Also, a set of modules for Inter-AS routing and Brokering could be managed successfully. A good number of solutions are provided for multipath routing issues in this sense of solving critical parameters like Brokering system of Inter-AS, the increase in response time to disaster, load balancing, reliability of the route between ASes with the new paradigm of SDN and enabling technologies. We believe that the advent of software enabled network and machine will not only enable scalable inter-domain routing with defined policies, but it is achievable with optimum result.